Comparison of esketamine versus dexmedetomidine for attenuation of cardiovascular stress response to double-lumen tracheal tube intubation: a randomized controlled trial - Liu, Chunyu; Zhang, Tianhua; Cao, Longhui; Lin, Wenqian (Frontiers in Cardiovascular Medicine, 2023)
The insertion of a double-lumen tracheal tube may cause a transient but more intense sympathetic response. We examined the effects of esketamine versus dexmedetomidine as an adjuvant to anesthesia induction to blunt double lumen tracheal (DLT) intubation induced cardiovascular stress response.In a randomized, double-blind trial, 78 adult patients scheduled for elective thoracotomy under general anesthesia requiring DLT intubation were enrolled. The patients were randomly divided into three groups: each group received one of the following drugs prior to induction of anesthesia: dexmedetomidine 0.8 µg/kg (Group A), esketamine 0.5 mg/kg (Group B), or normal saline (group C). The primary outcome was the incidence of a DLT intubation-related cardiovascular stress response, defined as an increase in mean arterial pressure or heart rate of > 30% above the baseline values. The secondary outcomes were changes in hemodynamic and cardiac function.The incidence of the response to cardiovascular stress was 23.1%, 30.8%, and 65.4% in groups A, B, and C, respectively. There was a significant decrease in intubation response in groups A and B in comparison with group C (P < 0.01); however, there was no significant difference between group A and group B (P > 0.05). Following the drug infusion and the induction of anesthesia, there This is a provisional file, not the final typeset article was a significant decrease in HR and cardiac output in group A compared with group B. In contrast, no significant differences were observed in the left ventricular ejection fraction or in stroke volume between the three groups during induction of anesthesia.Discussion: Esketamine 0.5 mg/kg and dexmedetomidine 0.8 µg/kg attenuate cardiovascular stress responses related to DLT intubation. As adjuvants to etomidate induction, they do not impair cardiac function. (ChiCTR1900028030)